The Relevance of Triangular Theory of Love in Devon Daniels’ Meet You in the Middle - Calista, Salsabila Nova; Pasopati , Rommel Utungga (CV. Tripe Konsultan, 2024)
This study investigates the profound love shared between the main characters, Kate Adam and Ben Mackenzie, in the novel